Submerged superoleophobic film as well as preparation method and application thereof

By etching the micro-nano structure on the copper mesh substrate and bonding modified nanoparticles, an efficient under-liquid superoleophobic film was prepared, which solved the problems of complex preparation, high cost and poor versatility of the existing film, and achieved efficient and low-cost oil-water separation and good membrane performance.

CN119701678APending Publication Date: 2025-03-28DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766692.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The preparation process of existing liquid ultralipophobic films is complex, costly and poor versatility, and the film has poor stain resistance, circulation, durability and oil-water separation efficiency.

Method used

The copper mesh substrate is etched to form a micro-nano structure, and the modified nanoparticles are bonded to the copper mesh substrate through polydopamine as a binder to prepare a liquid superoleophobic film with high efficiency oil-water separation performance.

Benefits of technology

It achieves efficient and low-cost oil-water separation. The membrane has good cycleability, durability and stability. It is suitable for industrial-scale production and exhibits high separation efficiency and flux under different oil-water ratios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701678A_ABST
    Figure CN119701678A_ABST
Patent Text Reader

Abstract

The invention provides an under-liquid super-oleophobic film which comprises a copper mesh substrate etched with a micro-nano structure and modified nanoparticles attached to the copper mesh substrate, and the modified nanoparticles are bonded to the copper mesh substrate through a binder. And the adhesive is polydopamine. The submerged superoleophobic membrane disclosed by the invention has relatively high separation flux and relatively high oil-water separation efficiency in separation of an oil-water mixed solution, and has extremely high submerged superoleophobic capacity; the preparation method is simple, low in cost, high in universality and suitable for industrial large-scale production, can be recycled in actual oil-water separation work, can still be stably filtered under the high-alkalinity condition, and has excellent recyclability, durability and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane materials, and in particular to an underwater super oleophobic membrane and a preparation method and application thereof. Background Art

[0002] There are many common methods for treating oily wastewater, such as gravity method, air flotation method, flocculation method, adsorption method, biological method, membrane separation method, etc. Traditional methods have disadvantages such as poor effect, high operating cost, limited practical application, and environmental pollution. Therefore, it is urgent to find efficient separation methods to meet modern needs, and membrane separation technology has the advantages of high selectivity, good oil-water separation efficiency, and simple operation.

[0003] At present, researchers have developed some regular lyophilic structures to change the surface wettability of materials, and have prepared a large number of special wettable membranes for oil-water separation (superhydrophobic / superoleophilic membranes, superhydrophilic / underwater superoleophobic membranes, Janus membranes, amphiphilic membranes, etc.). These membranes usually have rough structures at the micrometer or nanometer level, which can increase the contact angle when the oil droplets contact the surface, thereby enhancing the repelling effect of the oil droplets. Although the membrane separation method has great advantages, it also has some defects, such as poor anti-fouling performance of the membrane, weak circulation, and the oil-water separation efficiency will decrease with the increase of process operation time.

[0004] Most of the existing technologies use coating methods to prepare underwater superoleophobic films. Some coatings may be unstable in extreme temperatures, pH values ​​or chemical environments, affecting their performance; they may wear or degrade after long-term use, resulting in a decrease in their superoleophobic performance; and it is difficult to maintain the uniformity and consistency of the coating during large-scale production, which makes it difficult to scale up to industrial production; different coatings may have different separation effects when separating different oils, and need to be optimized for specific types of oils, and have poor versatility. The existing technology not only has a relatively complicated preparation process when preparing such membranes, but also often uses expensive fluorinated silanes and toxic solvents, which not only increases costs, but also has potential impacts on the environment. Therefore, it is now urgent to develop a simple preparation method to quickly prepare an underwater superoleophobic membrane that is more inclined to industrial applications, so as to achieve an extremely efficient and rapid water removal separation membrane. Summary of the invention

[0005] In view of the shortcomings of the prior art described above, the object of the present invention is to provide an underwater super oleophobic membrane and a preparation method and use thereof, so as to solve the problems in the prior art that the super oleophobic membrane preparation process is complicated, the cost is high, the versatility is poor, it is not suitable for large-scale production, and the membrane has poor anti-fouling properties, cyclability, durability, stability and oil-water separation efficiency.

[0006] In order to achieve the above-mentioned purpose and other related purposes, the present invention provides an underwater super oleophobic film and a preparation method and use thereof

[0007] The first aspect of the present invention provides an underwater super oleophobic film, which comprises a copper mesh substrate etched with a micro-nano structure and modified nanoparticles attached to the copper mesh substrate, wherein the modified nanoparticles are bonded to the copper mesh substrate via a binder; the binder is polydopamine.

[0008] Preferably, the micro-nano structure is formed on the surface of the copper mesh fiber and is in the shape of long and thin fluff.

[0009] Further preferably, the length of the micro-nano structure is 1 to 15 μm.

[0010] More preferably, the length of the micro-nano structure is 1 to 10 μm.

[0011] Most preferably, the length of the micro-nano structure is 5-10 μm, for example, 5-6 μm, 6-7 μm, 7-8 μm, 8-9 μm or 9-10 μm.

[0012] Preferably, the width of the micro-nano structure is 100-300 nm.

[0013] Further preferably, the width of the micro-nano structure is 100-150 nm, 150-200 nm, 200-250 nm, or 250-300 nm.

[0014] Preferably, the underwater superoleophobic membrane of the present invention is a hydrophilic-oleophilic membrane before being wetted with water, and becomes a hydrophilic-oleophobic membrane after being wetted with water.

[0015] In the present invention, a silane coupling agent is selected as a modifier to modify the nanoparticles.

[0016] Preferably, the modified nanoparticles are obtained by a silane coupling reaction between a silane coupling agent and nanoparticles in an aqueous ethanol solution.

[0017] Further preferably, the mass ratio of the nanoparticles to the silane coupling agent in the silane coupling reaction is 1:(5-20).

[0018] More preferably, the mass ratio of the nanoparticles to the silane coupling agent is 1:(5-15).

[0019] Most preferably, the mass ratio of the nanoparticles to the silane coupling agent may be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0020] More preferably, based on the amount of 1 g of nanoparticles added, the amount of aqueous ethanol added is 50 to 200 ml.

[0021] More preferably, based on the amount of 1 g of nanoparticles added, the amount of aqueous ethanol added is 50 to 150 ml.

[0022] More preferably, based on the amount of 1 g of nanoparticles added, the amount of aqueous ethanol added is 60-120 ml, for example, 60-80 ml, 80-100 ml, or 100-120 ml.

[0023] Preferably, the concentration of ethanol in the aqueous ethanol solution is 90% to 99%.

[0024] More preferably, the concentration of ethanol in the aqueous ethanol solution is 92% to 97%.

[0025] More preferably, the concentration of ethanol in the aqueous ethanol solution is 94% to 96%.

[0026] Preferably, the nanoparticles are one or two selected from titanium dioxide and silicon dioxide.

[0027] More preferably, the nanoparticles are titanium dioxide.

[0028] Preferably, the silane coupling agent is one or more selected from 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane and 3-aminopropylmethyldimethoxysilane.

[0029] More preferably, the silane coupling agent is 3-aminopropyltrimethoxysilane.

[0030] Preferably, the particle size of the nanoparticles is 10 to 100 nm.

[0031] More preferably, the particle size of the nanoparticles is 50 to 80 nm.

[0032] In some preferred embodiments of the present invention, the particle size of the nanoparticles is 50-60 nm.

[0033] Preferably, the mesh size of the copper mesh substrate is 100 to 500 meshes.

[0034] Further preferably, the mesh number of the copper mesh substrate is 300-500 meshes, for example, 300 meshes, 400 meshes or 500 meshes.

[0035] Preferably, the mass ratio of the binder to the modified nanoparticles is 1:(0.1-2).

[0036] More preferably, the mass ratio of the binder to the modified nanoparticles is 1:(0.2-1.5), for example, it can be 1:(0.2-0.5), 1:(0.5-1.0), 1:(1.0-1.5).

[0037] Preferably, the thickness of the underwater superoleophobic film is 0.1 to 5 mm.

[0038] Further preferably, the thickness of the underwater superoleophobic film is 1 to 2 mm.

[0039] Preferably, the underwater superoleophobic film has an underwater oil contact angle of >150°.

[0040] Further preferably, the underwater oil contact angle of the underwater superoleophobic film is 150° to 170°.

[0041] The underwater oil contact angle of the present invention is obtained by placing an underwater superoleophobic film in a water environment, dropping a drop of oil on the film, and measuring the surface contact angle between the oil and the film.

[0042] Preferably, the oil-water separation efficiency of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is greater than 99.0%.

[0043] Further preferably, the oil-water separation efficiency of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is 99.0% to 100%.

[0044] More preferably, the oil-water separation efficiency of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is greater than 99.2%.

[0045] Most preferably, the oil-water separation efficiency of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is greater than 99.5%.

[0046] In some preferred embodiments of the present invention, the oil-water separation efficiency of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is greater than 99.9%.

[0047] Preferably, the separation flux of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is ≥3700 Lm -2 h -1 .

[0048] Further preferably, the separation flux of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is 3700 to 15000 Lm -2 h -1 .

[0049] More preferably, the separation flux of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is ≥4000 Lm -2h -1 .

[0050] Most preferably, the separation flux of the underwater superoleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is ≥5000Lm -2 h -1 .

[0051] The second aspect of the present invention provides a method for preparing an underwater superoleophobic film, which comprises etching a micro-nano structure on a copper mesh substrate, and immersing the copper mesh substrate containing the micro-nano structure into a solution containing a) a binder or a monomer thereof, and b) modified nanoparticles.

[0052] Preferably, etching the micro-nano structure on the copper mesh substrate comprises immersing the copper mesh substrate in a mixed solution of sodium hydroxide solution and ammonium persulfate solution in a volume ratio of 1:(1-5) to etch the micro-nano structure on the copper mesh substrate.

[0053] Further preferably, the volume ratio of the sodium hydroxide solution to the ammonium persulfate solution is 1:(2-3).

[0054] Most preferably, the volume ratio of the sodium hydroxide solution to the ammonium persulfate solution is 1:(2.5-3).

[0055] Preferably, the concentration of the sodium hydroxide solution is 8 to 12 mol / L, the concentration of the ammonium persulfate solution is 0.1 to 0.5 mol / L, and the etching time is 10 to 30 min.

[0056] Further preferably, the concentration of the sodium hydroxide solution is 8-9 mol / L, 9-10 mol / L, 10-11 mol / L or 11-12 mol / L.

[0057] Further preferably, the concentration of the ammonium persulfate solution is 0.1-0.2 mol / L, 0.2-0.3 mol / L, 0.3-0.4 mol / L or 0.4-0.5 mol / L.

[0058] More preferably, the immersion etching time is 15 to 25 minutes.

[0059] Preferably, the modified nanoparticles are obtained by dissolving the nanoparticles and a silane coupling agent in an aqueous ethanol solution, dispersing the solution and centrifuging the solution.

[0060] Further preferably, the dispersion is carried out by using ultrasound to evenly disperse the nanoparticles and the silane coupling agent into a water ethanol solution.

[0061] In the present invention, the ultrasonic and centrifugal steps may be repeated for multiple cycles to allow the nanoparticles and the silane coupling agent to react fully.

[0062] Preferably, the immersion time of immersing the copper mesh substrate containing the micro-nano structure into the solution is 2 to 10 hours, more preferably 3 to 8 hours, and most preferably 5 to 6 hours.

[0063] Preferably, the solvent of the solution is a mixed solvent of ethanol and water.

[0064] Preferably, the solution further comprises Tris-hydrochloric acid buffer with a pH of 8-9.

[0065] In the present application, dopamine is polymerized to form polydopamine by dispersing dopamine in a mixed solution of ethanol and water containing a Tris-hydrochloric acid buffer solution at pH=8.8.

[0066] Preferably, in the mixed solvent of ethanol and water, the volume ratio of ethanol to water is (1-5):1, for example, it can be (1-2):1, (2-3):1, (3-4):1 or (4-5):1.

[0067] Preferably, in the solution containing the binder or its monomer and the modified nanoparticles, the concentration of the modified nanoparticles is 0.1 wt % to 1 wt %.

[0068] More preferably, the concentration of the modified nanoparticles is 0.1 wt% to 0.7 wt%.

[0069] Most preferably, the concentration of the modified nanoparticles is 0.3 wt% to 0.5 wt%.

[0070] Preferably, in the solution containing the binder or its monomer and the modified nanoparticles, the concentration of the binder is 0.1 wt% to 1 wt%.

[0071] More preferably, the concentration of the binder is 0.2 wt% to 0.8 wt%.

[0072] More preferably, the concentration of the binder is 0.3wt% to 0.8wt%, for example, 0.3wt% to 0.4wt%, 0.4wt% to 0.5wt%, 0.5wt% to 0.6wt%, 0.6wt% to 0.7wt%, 0.7wt% to 0.8wt%.

[0073] The third aspect of the present invention protects the use of the above-mentioned underwater superoleophobic membrane in the separation of oil-water mixture.

[0074] As described above, the underwater super oleophobic film and its preparation method and use of the present invention have the following beneficial effects:

[0075] 1. The underwater superoleophobic membrane of the present invention has a higher separation flux and a higher oil-water separation efficiency in the separation of an oil-water mixed solution, and has extremely strong underwater superoleophobic ability.

[0076] 2. The underwater superoleophobic membrane of the present invention can be recycled and can still filter stably under high alkaline conditions, and has excellent recyclability, durability and stability.

[0077] 3. The preparation method of the underwater superoleophobic film of the present invention is simple, low-cost, and highly versatile, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 Shown is a schematic diagram of a dead-end filtering device in the present invention.

[0079] Figure 2 Shown are schematic diagrams of the appearance morphology of the copper mesh substrate (CM), the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film (PDA@TiO2-NH2@Etch CM) in Example 2 of the present invention.

[0080] Figure 3 The copper mesh substrate (CM) in Example 3 of the present invention, the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film (PDA@TiO2-NH2@Etch CM) obtained by immersing in a TiO2-NH2 modified solution with an added mass fraction of 0.1wt%, 0.3wt%, 0.5wt%, and 0.7wt% are shown by scanning electron microscopy; wherein Figure 3 (A)-3(B) is the copper mesh substrate, Figure 3 (C)-3(D) is the copper mesh substrate after etching. Figure 3 (E)-3(F) is an underwater superoleophobic film under 0.1wt% TiO2-NH2, Figure 3 (G)-3(H) is an underwater superoleophobic film under 0.3wt% TiO2-NH2, Figure 3 (I)-3(J) is an underwater superoleophobic film under 0.5wt% TiO2-NH2, Figure 3 (K)-3(L) is an underwater superoleophobic film under 0.7wt% TiO2-NH2.

[0081] Figure 4 It shows the test results of oil-water separation efficiency and separation flux of different underwater superoleophobic membranes obtained after immersion in TiO2-NH2 modified solutions with added mass fractions of 0wt%, 0.1wt%, 0.3wt%, 0.5wt% and 0.7wt% in Example 3 of the present invention.

[0082] Figure 5Shown are the test results of oil-water separation efficiency and separation flux of the underwater superoleophobic membrane prepared using 300-mesh, 400-mesh and 500-mesh copper meshes as substrates in Example 4 of the present invention.

[0083] Figure 6 The three-dimensional morphological diagram of the copper mesh substrate (CM) of the present invention, the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film prepared in Example 5 under an atomic force microscope is shown; wherein, Figure 6 (A) is the copper mesh substrate, Figure 6 (B) is the copper mesh substrate after etching. Figure 6 (C) is an underwater superoleophobic film.

[0084] Figure 7 It is a schematic diagram showing the result of elemental composition analysis of the underwater superoleophobic film prepared in Example 5 of the present invention using energy dispersive spectroscopy (EDS).

[0085] Figure 8 Shown is a comparison chart of X-ray diffraction results of the copper mesh substrate (CM) of the present invention, the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film prepared in Example 5.

[0086] Fig. 9 It shows a comparison of infrared spectra of the copper mesh substrate (CM) of the present invention, the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film prepared in Example 5.

[0087] Fig.10 The figure shows the X-ray photoelectron spectrum comparison of the copper mesh substrate (CM) of the present invention, the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film prepared in Example 5; wherein, Fig.10 (a) is the characteristic peak of different elemental components on the film surface, Fig.10 (b) is the characteristic peak of Cu element, Fig.10 (c) is the characteristic peak of Ti element, Fig.10 (d) is the characteristic peak of O element.

[0088] Fig.11 Shown are the test results of the surface water contact angle and underwater oil contact angle of the copper mesh substrate (CM), the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film in Example 6 of the present invention.

[0089] Fig.12 Shown are the test results of the underwater surface oil contact angle of the underwater superoleophobic film and different types of oils in Example 6 of the present invention.

[0090] Fig.13Shown are the test results of the oil-water separation efficiency of the underwater superoleophobic membrane in an oil-water mixture formed by different types of oils and the oil content in the aqueous solution after separation in Example 6 of the present invention.

[0091] Fig.14 Shown are the separation flux test results of the underwater superoleophobic membrane in an oil-water mixture formed by different types of oil in Example 6 of the present invention.

[0092] Fig.15 Shown are the particle size distribution of the oil in water before and after separation of the oil-water mixture formed by n-hexane, cyclohexane and hexadecane in Example 6 of the present invention and the results of optical microscope observation.

[0093] Fig.16 Shown are the particle size distribution of the oil in water before and after separation of the oil-water mixture formed by petroleum ether and kerosene in Example 6 of the present invention and the results of optical microscope observation.

[0094] Fig.17 The results show the test results of using the underwater superoleophobic membrane in Example 7 of the present invention to cycle for 30 times and measuring its oil-water separation efficiency and separation flux after each separation operation.

[0095] Fig.18 It is a schematic diagram showing the morphology of the underwater superoleophobic film under a scanning electron microscope after 30 oil-water separation operations in Example 7 of the present invention.

[0096] Fig.19 Shown are the X-ray diffraction comparison graph and infrared comparison graph of the original underwater super oleophobic film without separation and the underwater super oleophobic film after 30 oil-water separation operations in Example 7 of the present invention; wherein, Fig.19 (A) is the X-ray diffraction comparison diagram, Fig.19 (B) is a comparison chart of infrared spectra.

[0097] Fig. 20 It is a schematic diagram showing the process of performing a sand impact test on an underwater superoleophobic film in Example 7 of the present invention.

[0098] Fig.21 The test results of the sand impact test on the underwater super oleophobic film in Example 7 of the present invention are shown; wherein Fig.21 (A) is the change in film weight and contact angle after the abrasive wear test was repeated 5, 10, 20, 30, 40 and 50 times. Fig.21 (B) is a schematic diagram of the morphology of the film under a scanning electron microscope after 50 abrasive wear tests.

[0099] Fig. 22 It is a schematic diagram showing the process of performing a weight wear test on an underwater superoleophobic film in Example 7 of the present invention.

[0100] Fig.23 The test results of the weight wear test on the underwater super oleophobic film in Example 7 of the present invention are shown; wherein Fig.23 (A) is the weight and contact angle change results of the film after the weight wear test was repeated 5, 10, 20, 30, 40 and 50 times. Fig.23 (B) is a schematic diagram of the morphology of the film under a scanning electron microscope after 50 weight wear tests.

[0101] Fig.24 The results of the oil-water separation efficiency and separation flux of the underwater superoleophobic membrane after immersion in alkaline solutions with pH values ​​of 8, 10, and 12 for 3 h, 6 h, and 12 h in Example 7 of the present invention are shown; wherein Fig.24 (A) is the oil-water separation efficiency test result of the membrane, Fig.24 (B) is the separation flux test result of the membrane.

[0102] Fig.25 The morphology of the underwater super oleophobic film in Example 7 of the present invention after being immersed in alkaline solutions with pH values ​​of 8, 10, and 12 for 12 hours under a scanning electron microscope is shown; wherein Fig.25 (A1) and 25 (A2) are scanning electron micrographs after immersion in an alkaline solution of pH 8 for 12 h. Fig.25 (B1) and 25(B2) are scanning electron micrographs after immersion in an alkaline solution with a pH of 10 for 12 h, and 25(C1) and 25(C2) are scanning electron micrographs after immersion in an alkaline solution with a pH of 12 for 12 h.

[0103] Fig.26 Shown are the test results of the pressure bearing capacity of the underwater superoleophobic film in Example 8 of the present invention for oil-water mixtures formed by different types of oils.

[0104] Fig. 27 It shows the detection result of the copper ion concentration in the aqueous solution after separation in Example 8 of the present invention. DETAILED DESCRIPTION

[0105] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0106] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0107] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0108] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0109] In view of the problems of complex preparation, poor separation effect, and decreased oil-water separation efficiency caused by clogging of existing oil-water separation membranes, the present invention selects a metal copper mesh as a substrate and uses a self-etching method to uniformly manufacture a micro-nano structure on the copper mesh substrate. In this application, polydopamine is used as a binder, TiO2 nanoparticles are used as functional particles, and 3-aminopropyltrimethoxysilane (APTMS) is a nanoparticle silane coupling agent. According to the Cassie-Raxter model, the Cu(OH)2 generated by etching provides a large-scale micro-roughness, and the TiO2 nanoparticles are used to improve the roughness and lyophilicity of the membrane; APTMS is grafted onto the TiO2 nanoparticles through a silane coupling reaction to enhance dispersibility and particle uniformity. Under the bonding effect of PDA, the two work together to enhance the superhydrophilicity, underwater superoleophobicity and oil-water separation ability of the metal copper mesh.

[0110] The membrane of the present invention exhibits super affinity for both oil and water in the air. When the membrane is moistened with water, the membrane exhibits super oleophobicity, which is suitable for separating oil-water mixtures. By utilizing the complete immiscibility of water and oil, the water film (hydrophilic oleophobic film after moistening) will intercept the oil on the membrane, and the water will pass through the water film, thereby separating the oil and water phases. In addition, after the oil is separated by the water film, the copper mesh will not be completely exposed to oil pollutants, thereby improving the durability. When using the membrane of the present invention to separate oil-water mixtures, it is only necessary to moisten the membrane with water in advance to perform the separation work, which is simple to operate, and in an oil-water mixture with an oil-water ratio of 1:99, the oil-water separation efficiency of the membrane can reach more than 99.0%, and the separation flux is ≥3700Lm -2 h -1 .

[0111] The test method for the oil-water separation efficiency and separation flux performance of the membrane in this application includes the following features:

[0112] a) Using an oil-in-water mixed system, the preparation of the oil-in-water mixed system: specifically, 1 mL of oil was added to 99 mL of deionized water, and the oil-in-water mixture was obtained after ultrasonic treatment for 1 h. Each test filtration was carried out at room temperature, and 20 ml of the oil-in-water mixture was used for filtration.

[0113] b) Testing by dead-end filtration method: The dead-end filtration device in this application is to match the mouths of two wide-mouth bottles relatively, and fix the membrane at the interface between the two as a filtration membrane, see Figure 1 During the test, the oil-in-water mixture is added to one of the wide-mouth bottles, a water-wetted membrane is placed at the mouth of the bottle, and the other empty wide-mouth bottle is inverted. The mouths of the two wide-mouth bottles are aligned and clamped with a clamp, and then the whole is inverted. Then, the water in the one wide-mouth bottle will flow through the membrane into the other empty wide-mouth bottle to obtain the filtrate.

[0114] The separation flux is calculated by formula (1); the separation efficiency is calculated by formula (2). The separation flux is represented by J, V is the volume of filtrate passing through the membrane (L), T and S are the separation time (in hours) and the effective filtration area (in m 2 ); the separation efficiency is represented by R, Cp is the mass concentration of oil in the filtrate after separation, Cf is the mass concentration of oil in the water-in-oil mixture before separation, (1) (2)

[0115] In the following specific embodiments:

[0116] The copper metal used was purchased online from Jinanjia Electronic Materials Business Department in Yushan Town, Kunshan City;

[0117] The TiO2 used was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a particle size of 60 nm.

[0118] Example 1

[0119] This embodiment provides a method for preparing an underwater super oleophobic film, comprising the following steps:

[0120] Step 1: Prepare a copper mesh substrate with a microstructure on the surface by using a self-etching method.

[0121] A metal copper mesh (CM) with a mesh size of 300-500 mesh and a size of 3×3cm was ultrasonically cleaned with acetone and anhydrous ethanol solution respectively, and the total cleaning time was 3 hours to obtain a clean copper mesh. Sodium hydroxide and ammonium persulfate were used as raw materials to prepare a 10M sodium hydroxide solution and a 0.18M ammonium persulfate solution respectively, and stirred at room temperature for 6 hours until the powder was completely dissolved. 32ml of sodium hydroxide solution was added to 88ml of ammonium persulfate solution and stirred evenly to form a mixed solution. After the clean copper mesh was soaked in the mixed solution for 20 minutes, it was taken out and washed with deionized water, and dried in a 60℃ oven for use to obtain the etched copper mesh substrate, which was recorded as Etch CM.

[0122] Step 2: Nanoparticle modification.

[0123] First, 5 g of TiO2 powder and 50 ml of APTMS were placed in a bottle, and 500 ml of aqueous ethanol (concentration of 95%) was added. The mixture was stirred at room temperature for 3 h until it was completely dissolved. Ultrasonication was performed for 30 min to ensure complete dispersion, and centrifugation was performed. The ultrasonication and centrifugation process was repeated three times to ensure that the nanoparticles were uniformly modified. After the last centrifugation, the deposited modified nanoparticles were separated and dried to obtain the modified nanoparticles, which were recorded as TiO2-NH2.

[0124] Step 3: Prepare the underwater superoleophobic film by adhesion method.

[0125] 0.2g dopamine (DA) and an appropriate amount of TiO2-NH2 nanoparticles are dissolved in a mixed solution formed by 28ml ethanol and 14ml water, 2mL of Tris-hydrochloric acid buffer with pH = 8.8 is added, and stirred for 6h until the solution is brown-black. In this process, only the amount of modified nanoparticles is controlled to optimize the technology, and a TiO2-NH2 modified solution with a mass fraction of 0.1wt%, 0.3wt%, 0.5wt%, and 0.7wt% is obtained, in which dopamine will polymerize to form polydopamine (PDA). The previously prepared Etch CM mesh is immersed in different mixed modified solutions, taken out after soaking for 6h, washed with deionized water and dried to obtain a finished submerged super oleophobic film, and the prepared submerged super oleophobic film is recorded as PDA@TiO2-NH2@Etch CM.

[0126] Example 2

[0127] The thickness and appearance of the underwater superoleophobic film prepared in Example 1 of the present invention were tested.

[0128] The specific thickness test is carried out using a thickness measuring instrument, and the underwater superoleophobic film is measured 5 times at different positions to obtain an average value. The test shows that the thickness of the underwater superoleophobic film prepared by the present invention is between 1 and 2 mm.

[0129] Furthermore, the appearance of the copper mesh substrate (CM), the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film (PDA@TiO2-NH2@Etch CM) were observed, and the results are as follows: Figure 2 shown.

[0130] Example 3

[0131] In this embodiment, based on Example 1, a 500-mesh copper mesh is used as the substrate, and the copper mesh etching time is 20 minutes. The etched copper mesh substrate is immersed in TiO2-NH2 modified solutions with added mass fractions of 0.1wt%, 0.3wt%, 0.5wt%, and 0.7wt%, respectively, to prepare an underwater superoleophobic film.

[0132] The morphology of the different submerged superoleophobic films prepared above was observed using a scanning electron microscope. Figure 3 As shown. Figure 3 Compared with the copper mesh substrate in (A)-3(B), Figure 3 (C)-3(D) A uniform and dense micro-nano structure is formed on the surface of the etched copper mesh substrate; Figure 3 After (E)-3(F) was immersed in a modified solution with a mass fraction of 0.1wt% TiO2-NH2, the number of nanoparticles adhering to the membrane surface was small. As the mass fraction of TiO2-NH2 in the modified solution increased, the number of nanoparticles adhering to the membrane surface increased, and the roughness of the membrane increased accordingly. Figure 3 (K)-3(L) shows that when the mass fraction of TiO2-NH2 in the modified solution increases to 0.7wt%, the number of adhered nanoparticles increases, and the microstructure on the copper mesh substrate is almost covered by the aggregation of nanoparticles, which in turn leads to a decrease in roughness and the occurrence of pore blocking.

[0133] The oil-water separation efficiency and separation flux of the different underwater superoleophobic membranes prepared in this example were tested. 1 ml of five different types of oil (n-hexane, cyclohexane, hexadecane, petroleum ether and kerosene) were added to 99 mL of deionized water to prepare water-in-oil mixtures containing different types of oil. The oil-water separation efficiency and separation flux of the membrane were tested using the above method.

[0134] Specific test results such as Figure 4As shown, the horizontal axis represents the different underwater superoleophobic membranes obtained after soaking in modified solutions of TiO2-NH2 with added mass fractions of 0wt%, 0.1wt%, 0.3wt%, 0.5wt%, and 0.7wt%, and the vertical axis represents the oil-water separation efficiency (left) and separation flux (right) of different membranes. The results show that with the increase of the mass fraction of TiO2-NH2 in the modified solution, the oil-water separation efficiency and separation flux of the membrane gradually increase, and reach the optimal separation efficiency and separation flux at 0.5wt% addition; continue to increase the mass fraction of TiO2-NH2 in the modified solution, the separation efficiency and separation flux of the membrane decrease instead. Compared with the membrane obtained by soaking in a modified solution with an addition amount of 0wt% TiO2-NH2, the membrane oil-water separation efficiency obtained after soaking in a modified solution with an addition amount of 0.5wt% TiO2-NH2 can reach more than 99.9%, and the separation flux is close to 6000Lm -2 h -1 .

[0135] Example 4

[0136] In this Example 4, the modified solution with a mass fraction of TiO2-NH2 of 0.5 wt% in Example 1 was selected, and copper mesh substrates with different mesh sizes were used to investigate the effect of the copper mesh pore size on the oil-water separation efficiency of the underwater superoleophobic membrane. The specific membrane preparation process is the same as that in Example 1.

[0137] The above method was used to test the oil-water separation efficiency and separation flux of the underwater superoleophobic membrane prepared by copper mesh with different mesh sizes. The results are as follows: Figure 5 As shown. The results show that as the number of copper meshes increases, the copper mesh aperture becomes smaller, so the separation flux of the membrane gradually decreases, but the oil-water separation efficiency gradually increases. The submerged super oleophobic membrane prepared by the copper mesh of different meshes in the present embodiment is suitable for oil-water separation work. In actual work, if there is a high separation efficiency demand, a copper mesh with a larger mesh number is used, and if there is a higher flux demand, a copper mesh with a small mesh number is selected, but the oil-water separation efficiency of all membranes refers to GB8978 "Comprehensive Sewage Discharge Standard" rule to meet the limit value of China's wastewater discharge Class A standard.

[0138] Example 5

[0139] Based on the comprehensive consideration of the influence of the copper mesh number and the mass fraction of TiO2-NH2 in the modified solution on the membrane morphology and oil-water separation performance in the above Examples 3-4, the copper mesh number was selected as 500 mesh and the mass fraction of TiO2-NH2 in the modified solution was 0.5wt% for the preparation of the underwater super oleophobic membrane. The specific preparation method is the same as that in Example 1, and the three-dimensional morphology, elemental composition, etc. of the prepared underwater super oleophobic membrane (PDA@TiO2-NH2@Etch CM) are investigated.

[0140] First, an atomic force microscope was used to observe the three-dimensional morphology of the copper mesh substrate (CM), the etched copper mesh substrate (Etch CM), and the submerged superoleophobic film (PDA@TiO2-NH2@Etch CM) prepared by immersing in a modified solution with a mass fraction of 0.5 wt % TiO2-NH2 in this embodiment. The specific observation results are shown in FIG. Figure 6 As shown. The copper mesh substrate (CM) showed a smooth interface due to the lack of etching, and the roughness (Ra) value was only 134nm; the roughness of the etched copper mesh (Etch CM) reached 786nm, and it can be seen that the interface presents a uniform micro-nano structure; when the modified nanoparticles are attached, the roughness of the membrane is greatly increased, reaching 1034nm. High surface roughness and low surface energy are important factors for manufacturing underwater oleophobic surfaces, proving that the membrane prepared by the present invention has a high hydration capacity, which helps the membrane surface to adsorb water molecules to form a hydration layer. The hydration layer can inhibit the nonspecific interaction between oil droplets and the membrane surface, thereby reducing the contamination of the surface by oil droplets.

[0141] Furthermore, the elemental composition of the prepared superoleophobic film was analyzed by energy dispersive spectroscopy (EDS). Figure 7 shown. Figure 7 (A) is the surface morphology of the membrane under a scanning electron microscope. Figure 7 (B)-7(G) are different element morphologies on the membrane. The results show that each element in the area irradiated by the electron microscope at a relatively low magnification exhibits excellent uniformity, indicating that the present invention attaches copper hydroxide and modified nanoparticles to the copper mesh substrate through two processes of etching and adhesion. The surface of the underwater superoleophobic membrane (PDA@TiO2-NH2@Etch CM) prepared by this method is regular, and each element is uniformly attached, which is beneficial to the stability and separation of the membrane in the subsequent oil-water separation work.

[0142] Furthermore, X-ray diffraction was used to analyze the copper mesh substrate (CM), the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film (PDA@TiO2-NH2@Etch CM). Figure 8 As shown in the figure, the results show that after etching, the XRD of the etched copper mesh substrate (Etch CM) and the underwater superoleophobic film (PDA@TiO2-NH2@Etch CM) show completely different peaks compared with the copper mesh (CM). After analysis, the newly added peaks indicate that the orthorhombic phase Cu(OH)2 forms nanowire crystals on the surface of the copper mesh. Figure 8 The strong peaks marked with triangles are the diffraction peaks of copper, and the * indicates that the copper mesh generates the Cu(OH)2 diffraction peak after etching. After the modified nanoparticles are attached, the XRD diffraction peaks of copper hydroxide are still retained, which indicates that the introduction of modified TiO2 nanoparticles does not eliminate the rough structure of copper hydroxide generated by etching.

[0143] Furthermore, the copper mesh substrate (CM), the etched copper mesh substrate (Etch CM) and the superoleophobic film (PDA@TiO2-NH2@Etch CM) were analyzed by infrared spectroscopy. Fig. 9 The results show that the prepared superoleophobic film retains the characteristic peak of Etch CM. The peak at 1480 cm-1 in the spectrum after modification with PDA@TiO2-NH2 is -1 A new peak appears at 1335 cm -1 The band at 1570 cm-1 in the spectrum of PDA@TiO2-NH2@Etch CM is attributed to the stretching vibration of phenolic OH in PDA. -1 A new peak appeared at 2920cm -1 and 2850cm -1 The peak at is the stretching vibration of -CH2 in the grafted carbon chain. This shows that the modified nanoparticles have been successfully adhered to the copper mesh substrate by PDA.

[0144] Furthermore, X-ray photoelectron spectroscopy (XPS) was used to analyze the chemical state and elemental composition of the prepared superoleophobic film surface. Fig.10 As shown, Fig.10 The XPS full spectrum of (a) shows the surface composition of different samples. After modification, a Ti peak is added, and the intensities of the O peak and C peak increase. There are obvious characteristic peaks near 459.7, 284.6, 531.8 and 942.3 eV, which are attributed to Ti 2p, C 1s, O 1s and Cu 2p, respectively. Further detailed analysis of each component is carried out. Fig.10 (b) All peaks shown by Cu 2p are characteristic peaks of copper hydroxide, and there are no other impurity peaks. Fig.10 The two characteristic peaks at 464.5 and 458.7 eV in (c) correspond to Ti2p 1 / 2 and Ti2p 3 / 2 . Fig.10 There are three obvious peaks at 530.6, 531.6 and 532.8 eV in (d), corresponding to the oscillation peaks of OC, O═C and O-Ti, respectively, indicating that the catechol structure in PDA is successfully combined with TiO2. These results also prove the successful preparation of PDA@TiO2-NH2@Etch CM.

[0145] Example 6

[0146] The hydrophilicity, underwater oleophobicity and oil-water separation performance of the underwater superoleophobic membrane (PDA@TiO2-NH2@Etch CM) prepared in Example 5 were tested.

[0147] According to the image profile analysis, the surface water contact angle and underwater oil contact angle of the copper mesh substrate (CM), the etched copper mesh (Etch CM) and the underwater super oleophobic film (PDA@TiO2-NH2@Etch CM) were tested using a contact angle meter. The oil was n-hexane. Five different areas of each sample were measured and the average value was taken. The test results are shown in Figure 2. Fig.11 The results show that although the original copper mesh has a certain underwater oleophobicity, it does not meet the basic separation requirements. After etching, although it has reached a rough state, its hydrophilicity is still insufficient. The underwater super oleophobic membrane prepared in Example 5 has strong hydrophilicity and underwater super oleophobicity.

[0148] Furthermore, the contact angle of the underwater super oleophobic film prepared in Example 5 on different oil surfaces underwater was tested using the above method. Specifically, the film was placed in a water environment, and oil drops were dripped onto the film using a dropper to test the contact angle between the oil drop and the film. The test results are shown in FIG. Fig.12 The results show that the underwater super oleophobic film prepared by the present invention has strong oleophobic properties to different types of oils.

[0149] The above method was further used to test the separation ability of the underwater super oleophobic membrane prepared in Example 5 for different oil-water mixtures. The results are as follows: Fig.13 and Fig.14 shown.

[0150] Fig.13 The horizontal axis represents different types of oil, and the vertical axis represents the oil-water separation efficiency (left) and the oil content in the water after separation (right). The test method for the oil content in the water after separation is to use a total organic carbon (TOC) measuring instrument. The principle is: oxidize the total organic carbon in the aqueous solution into carbon dioxide and measure its content; use the corresponding relationship between the carbon content of carbon dioxide and total organic carbon to quantitatively measure the total organic carbon in the aqueous solution.

[0151] The results show that the underwater superoleophobic membrane prepared by the present invention can achieve an oil-water separation efficiency of more than 99.9% for oil-water mixtures formed by different types of oils, and the oil content in the water after separation is less than 10ppm, which meets the highest Class A emission standards.

[0152] Fig.14 The horizontal axis represents different types of oil, and the vertical axis represents the separation flux. The results show that the separation flux of the submerged superoleophobic membrane prepared by the present invention for different types of oil can reach 5900Lm -2 h -1The above has a higher separation flux.

[0153] Furthermore, n-hexane, cyclohexane, hexadecane, petroleum ether and kerosene were selected as the oil phase, and different oil-water mixtures were prepared according to the oil-water volume ratio of 1:99. The underwater superoleophobic membrane prepared in Example 5 was used to separate the different oil-water mixtures, and the particle size distribution before and after separation was observed. The conditions of the solution before and after separation were observed under an optical microscope. The results are as follows: Fig.15 and Fig.16 The results show that before oil-water separation, an obvious oil particle size distribution can be observed in the solution, but after oil-water separation, no oil particle size distribution can be observed in the solution (upper right corner of the particle size distribution graph), indicating that after separation, the oil content in water is greatly reduced. Microscope observation results show that a large number of oil droplets can be observed in the solution before separation, but no oil droplets can be observed in the solution after separation.

[0154] The above results collectively prove that the underwater superoleophobic membrane prepared in the present application has a strong oil-water separation ability for different types of oil-water mixtures, and the oil content in the water after separation is extremely low. It is suitable for separating different types of oil-water mixtures and has strong versatility.

[0155] Example 7

[0156] The reusability, wear resistance, and stability of the underwater superoleophobic film (PDA@TiO2-NH2@Etch CM) prepared in Example 5 were tested.

[0157] The reusability of the underwater super oleophobic membrane of the present invention was tested. The underwater super oleophobic membrane prepared in Example 5 was used to separate an oil-water mixture formed by n-hexane and water with an oil-water ratio of 1:99. Before each separation cycle, the membrane was wetted with water in advance for use. After one use, it was washed and dried, and the separated membrane was used to separate a new oil-water mixture. The separation was repeated 30 times, and the oil-water separation efficiency and separation flux of the membrane in each separation work were tested. The results are shown in FIG. Fig.17 The results show that after 30 separations, the oil-water separation efficiency of the membrane is still > 99.5%, and the separation flux exceeds 6000Lm -2 h -1 .

[0158] Furthermore, the underwater superoleophobic film after 30 oil-water separation operations was observed under a scanning electron microscope, and its morphology was as follows: Fig.18 As shown, after 30 oil-water separation operations, dense nanoparticles are still evenly distributed on the surface of the underwater superoleophobic film.

[0159] In addition, the contact angle of the underwater superoleophobic film after 30 oil-water separation operations was measured, and its underwater oil contact angle was 159.4°, indicating that it still has strong underwater oleophobicity after 30 oil-water separation operations.

[0160] The underwater superoleophobic membrane after 30 oil-water separations and the original underwater superoleophobic membrane without separation were further characterized by XRD diffraction and infrared. The test results are as follows: Fig.19 A and 19B. The results show that after 30 oil-water separation operations, the underwater superoleophobic film still retains the characteristic absorption peak of the original film.

[0161] Figure 17 to Figure 19 The results together show that after 30 oil-water separation operations, the underwater superoleophobic membrane of the present invention still has a high oil-water separation efficiency, a high separation flux and strong underwater oleophobicity, and can be recycled many times, which is beneficial to saving energy and reducing costs.

[0162] The wear resistance of the underwater super oleophobic film of the present invention was tested. First, the underwater super oleophobic film prepared in Example 5 was subjected to an abrasive wear test. Specifically, the mechanical durability of the underwater super oleophobic film was tested by a sand impact test. The specific experimental process is as follows: Fig. 20 As shown. In the sand impact test, fine sand particles of 500 to 1000 μm are impacted on the membrane from a height of 30 cm at an inclination of 30°. After being impacted by 300 g of sand for a certain number of times (5, 10, 20, 30, 40, 50), the worn membrane is weighed by the weighing method and the weight is recorded as m x , the weight of the film before wear is recorded as m0. The specific test results are as follows Fig.21 As shown in (A), the horizontal axis represents the number of cyclic impacts of sand particles, and the vertical axis represents the mass ratio of the membrane before and after wear (left) and the submerged oil contact angle of the membrane. The results show that after 50 cycles of wear, the mass of the membrane changes very little, and the contact angle also changes very little, which indicates that the membrane can still maintain submerged superoleophobicity after a certain amount of mechanical wear. The scanning electron microscope image of the membrane after 50 wears is shown in Fig.21 (B) The results show that after 50 times of sand abrasion, the surface morphology of the membrane is good, proving that it has excellent anti-wear performance.

[0163] The wear resistance of the membrane was further tested by a weight wear test. Specifically, a 20g weight was placed on the non-woven fabric and pressed vertically on the membrane. The membrane was stretched back and forth horizontally at a uniform speed. The entire distance was controlled within 15cm. The test was also repeated for a certain number of times (5, 10, 20, 30, 40, 50). The specific experimental process of the weight wear test is as follows: Fig. 22 The specific test results are shown in Fig.23As shown in the figure, after multiple cycles of wear, the mass of the film changes little, and the contact angle also changes little. The film still shows excellent wear resistance in the weight wear test with strong wear force, and the lateral force is relatively stronger than the laminated film, which also proves that the underwater super oleophobic film of the present invention has strong wear resistance to friction loss in actual use.

[0164] The stability of the underwater super oleophobic membrane of the present invention was tested. Several underwater super oleophobic membranes prepared in Example 5 were taken and immersed in alkaline solutions of pH 8, 10, and 12, respectively. They were taken out after being immersed in the alkaline solution of each pH for 3 h, 6 h, and 12 h, and the oil-water separation efficiency and separation flux of the membrane for an oil-water mixture formed by n-hexane and water with an oil-water ratio of 1:99 were measured. The specific test results are shown in FIG. Fig.24 shown.

[0165] The results show that the submerged superoleophobic membrane of the present invention can maintain good stability in an alkaline solution with a pH of 8. After immersion for 3 h, 6 h and 12 h, the oil-water separation efficiency and separation flux of the membrane remain almost unchanged, reaching an oil-water separation efficiency of 99.9% and a separation flux of 5900 L / min. -2 h -1 When the submerged superoleophobic membrane was immersed in an alkaline solution with a pH of 10, the oil-water separation efficiency of the membrane remained almost unchanged and reached about 99.9 after immersion for 3, 6, and 12 hours, but the membrane flux decreased slightly with the extension of the immersion time. After immersion for 12 hours, the membrane separation flux was 5200 Lm -2 h -1 When the underwater superoleophobic membrane was immersed in an alkaline solution with a pH of 12, the oil-water separation efficiency and membrane flux of the membrane decreased to varying degrees after immersion for 3h, 6h and 12h. After immersion for 3h, the oil-water separation efficiency of the membrane was about 99.9%, and the membrane flux was 5500Lm -2 h -1 After immersion for 6 hours, the oil-water separation efficiency of the membrane is about 99.8%, and the membrane flux is 4500Lm -2 h -1 After immersion for 12 hours, the oil-water separation efficiency of the membrane is about 99.6%, and the separation flux of the membrane is 4000Lm -2 h -1 about.

[0166] The underwater superoleophobic film was observed by scanning electron microscopy after being immersed in the above alkaline solutions of different pH values. Fig.25 The results show that as the pH increases, the aggregation of nanoparticles on the membrane will cause pore blocking, thus leading to a decrease in membrane separation flux.

[0167] The above results confirm that the underwater superoleophobic membrane of the present invention has strong stability in an alkaline environment and can normally perform the separation work of oil-water mixture.

[0168] Example 8

[0169] The pressure bearing capacity of the underwater superoleophobic membrane prepared in Example 5 of the present invention for different types of oils was tested. The specific method was to fix the wetted membrane in a dead-end device, add 2 to 3 drops of water to ensure that a layer of water was formed on the membrane surface, add a certain volume of oil to the membrane, and add it in sequence until the oleophobic capacity of the membrane could not bear the gravity of the oil, that is, when oil drop penetration occurred, stop adding and record the volume. According to formula (3) E p =mgh to calculate the pressure that the membrane can withstand, where m is the mass, g is the acceleration due to gravity, h is the liquid level, and Ep is the gravitational potential energy.

[0170] The work of gravitational potential energy in formula (3) is regarded as the maximum pressure value that the membrane can bear. The test results are as follows: Fig.26 As shown in the figure, the vertical axis represents the pressure when oil penetration occurs, that is, the maximum pressure value that the membrane can bear for oil. The results show that the pressure bearing capacity of the membrane for different types of oil is greater than 1.0 kPa, which proves that the underwater superoleophobic membrane prepared in Example 5 has excellent bearing capacity for different types of oil.

[0171] Furthermore, the submerged superoleophobic membrane prepared in Example 5 was used to separate an oil-water mixture formed by n-hexane and water with an oil-water ratio of 1:99, and the copper ion concentration in the separated solution was investigated. Two sample solutions were taken for testing. Specifically, the separated solution was scanned using inductively coupled plasma (ICP), and the copper ion concentration in the final separated solution to be tested was calculated based on the copper ion concentration standard curve. The results are shown in FIG. Fig. 27 As shown in the figure, the horizontal axis is the number of the solution to be tested, and the vertical axis is the content of copper ions. The results show that the concentration of copper ions in the solution after separation is at the trace ppt level, proving that the underwater superoleophobic membrane will not introduce copper ions into the solution during the separation process.

[0172] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A submerged superoleophobic film, characterized in that: The underwater super oleophobic film comprises a copper mesh substrate etched with a micro-nano structure and modified nanoparticles attached to the copper mesh substrate, wherein the modified nanoparticles are bonded to the copper mesh substrate via a binder; the binder is polydopamine.

2. The underwater super oleophobic film according to claim 1, characterized in that The modified nanoparticles are obtained by silane coupling reaction between a silane coupling agent and nanoparticles in an aqueous ethanol solution; the nanoparticles are one or two selected from titanium dioxide and silicon dioxide; the silane coupling agent is one or more selected from 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane and 3-aminopropylmethyldimethoxysilane; and / or, the mesh number of the copper mesh substrate is 100-500 meshes; and / or, the mass ratio of the binder to the modified nanoparticles is 1:(0.1-2); and / or, the micro-nano structure is formed on the surface of the copper mesh fiber and is in the form of slender villi; and / or, the underwater superoleophobic film is a hydrophilic-oleophilic film before being wetted with water, and is a hydrophilic-oleophobic film after being wetted with water.

3. The underwater super oleophobic film according to claim 2, characterized in that: The mass ratio of the nanoparticles to the silane coupling agent in the silane coupling reaction is 1:(5-20); and / or, based on the addition amount of 1g of the nanoparticles, the addition amount of the aqueous ethanol is 50-200ml; and / or, the concentration of ethanol in the aqueous ethanol solution is 90%-99%; and / or, the particle size of the nanoparticles is 10-100nm; and / or, the length of the micro-nano structure is 1-15μm, and the diameter of the micro-nano structure is 100-300nm.

4. The underwater super oleophobic film according to claim 1, characterized in that: The thickness of the underwater super oleophobic film is 0.1 to 5 mm; And / or, the underwater oil contact angle of the underwater superoleophobic film is greater than 150°.

5. The underwater super oleophobic film according to claim 1, characterized in that: The oil-water separation efficiency of the underwater super oleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is greater than 99.0%; and / or the separation flux of the underwater super oleophobic membrane for an oil-water mixed solution with an oil-water ratio of 1:99 is greater than or equal to 3700 Lm -2 h -1 .

6. A method for preparing an underwater super oleophobic film according to any one of claims 1 to 5, characterized in that: The method comprises etching a micro-nano structure on a copper mesh substrate, and immersing the copper mesh substrate containing the micro-nano structure into a solution containing a) a binder or a monomer thereof, and b) modified nanoparticles.

7. The preparation method according to claim 6, characterized in that: Etching a micro-nano structure on a copper mesh substrate comprises: immersing the copper mesh substrate in a mixed solution of a sodium hydroxide solution and an ammonium persulfate solution in a volume ratio of 1:(1-5) to etch the micro-nano structure on the copper mesh substrate; preferably, the concentration of the sodium hydroxide solution is 8-12 mol / L, the concentration of the ammonium persulfate solution is 0.1-0.5 mol / L, and the immersion time is 10-30 min.

8. The preparation method according to claim 6, characterized in that: The modified nanoparticles are obtained by dissolving the nanoparticles and the silane coupling agent in a water ethanol solution, dispersing them and centrifuging them; and / or the solvent of the solution is a mixed solvent of ethanol and water; and / or the soaking time is 2 to 10 hours.

9. The preparation method according to claim 8, characterized in that: The concentration of the aqueous ethanol solution is 90% to 99%; and / or, in the mixed solvent of ethanol and water, the volume ratio of ethanol to water is (1 to 5): 1; and / or, in the solution containing the binder or its monomer and the modified nanoparticles, the concentration of the modified nanoparticles is 0.1wt% to 1wt%, and the concentration of the binder is 0.1wt% to 1wt%.

10. Use of the underwater superoleophobic membrane according to any one of claims 1 to 5 in separation of oil-water mixture.